2022
DOI: 10.1002/joom.1225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the U.S.–China trade war on the operating performance of U.S. firms: The role of outsourcing and supply base complexity

Abstract: Multinational corporations have benefited tremendously from free trade in the past few decades. However, the dynamism of international relations, paired with the global recession, has rekindled the debate over frictionless trade. In this study, we examine how trade friction, created by tariff trade barriers, affects the operational performance of domestic firms which source from the affected countries. We also investigate how various supply chain characteristics and strategies can moderate the impact of such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 109 publications
(213 reference statements)
0
17
0
Order By: Relevance
“…The second stream investigates supply chain complexity in terms of upstream, downstream and internal complexities according to their origins (Bozarth et al, 2009;Akın Ates ¸et al, 2021). The third stream focuses Reconciling effects of intelligent manufacturing on upstream complexity and divides it into more detailed sub-categories (Brandon-Jones et al, 2014b;Bode and Wagner, 2015;Wiedmer et al, 2021;Delbufalo, 2022;Fan et al, 2022), such as horizontal, vertical and spatial complexities according to the number of tiers, the number of members in each tier and geographic distances among different members, respectively (Brandon-Jones et al, 2014b;Bode and Wagner, 2015;Lu and Shang, 2017;Sharma et al, 2019;Wiedmer et al, 2021;Delbufalo, 2022;Fan et al, 2022).…”
Section: Supply Chain Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…The second stream investigates supply chain complexity in terms of upstream, downstream and internal complexities according to their origins (Bozarth et al, 2009;Akın Ates ¸et al, 2021). The third stream focuses Reconciling effects of intelligent manufacturing on upstream complexity and divides it into more detailed sub-categories (Brandon-Jones et al, 2014b;Bode and Wagner, 2015;Wiedmer et al, 2021;Delbufalo, 2022;Fan et al, 2022), such as horizontal, vertical and spatial complexities according to the number of tiers, the number of members in each tier and geographic distances among different members, respectively (Brandon-Jones et al, 2014b;Bode and Wagner, 2015;Lu and Shang, 2017;Sharma et al, 2019;Wiedmer et al, 2021;Delbufalo, 2022;Fan et al, 2022).…”
Section: Supply Chain Complexitymentioning
confidence: 99%
“…, 2014b; Bode and Wagner, 2015; Wiedmer et al. , 2021; Delbufalo, 2022; Fan et al. , 2022), such as horizontal, vertical and spatial complexities according to the number of tiers, the number of members in each tier and geographic distances among different members, respectively (Brandon-Jones et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From a politico-economic prism, the view of American regarding trade war has also been studied, and the findings reveal that Americans are divided over US–China trade war though 76% of the surveyed adults supported trade with China (Jin et al , 2022). In addition, by applying difference in difference technique, it was found that trade war has a negative impact for US firms with high outsourcing (Fan et al , 2022). Recent findings on the decrease in China’s exports to the USA are not surprising, and the specific fall in the exports has been reported to be 16.47% associated with quantity fall while price remain unchanged, relatively (Jiang et al , 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, the authors found that the ban benefited ZTE's competitors, whose stock prices advanced by 1.34%. Fan et al (2022) examined the impact of the 2018 US-China trade war on US firms' operating performance. Their DiD analysis revealed that US firms suffered from an increase in days of inventory and lower profitability because of the trade war.…”
Section: Global Oscm Studies Incorporating a Political Economy Perspe...mentioning
confidence: 99%